KONSEP AKHLAK PENDIDIK (TELAAH SYAIR QAD KAFANI KARYA IMAM ABDULLAH AL-HADDAD DAN KITAB TA’LIM MUTA’ALLIM) - Rachmad Hidayat; Amir Maliki Abitolkha; Abdul Manan; Moh Faizin; Imam Syafi'i (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
Qad Kafani's poetry, which is thick with Sufi moral nuances, needs to be applied for the quality of educators who are in accordance with the spirit of Islamic education, namely scientific responsibility and being able to implement it. This study aims to find out the meaning of the morals of educators in poetry and then look for the relationship in the Ta'lim Muta'allim book. This type of research is qualitative library research using a phenomenological approach, manuscript study research models, content analysis techniques through the interpretation stage, deduction of the poetry of Qad Kafani, induction of the book of Ta'lim Muta'allim, and comparison of the relationship between the two concepts. This research produced 8 educational moral concepts from the perspective of Qad Kafani's poetry, namely faith, indigent, trustful, patient, raja', tawaduk, istikamah, husnuzan and 14 educational moral concepts in the Ta'lim Muta'allim book, namely not being greedy, taking care of oneself, tawaduk, pious, warak, older, more mature, dignified, polite, patient, compassionate, advisory, not spiteful, not in dispute or bickering. Both of these concepts have specific similarities in relevance to humility and patience as well as differences that are still within the scope of the noble character of the Sufism dimension and complement each other.